Genotype‐guided drug prescribing: a systematic review and meta‐analysis of randomized control trials. (22nd July 2015) - Goulding, Rebecca; Dawes, Diana; Price, Morgan; Wilkie, Sabrina; Dawes, Martin
<x xml:space="preserve">Abstract</x> Aim Adverse drug events lead to increased morbidity, mortality and health care costs. Pharmacogenetic testing that guides drug prescribing has the potential to reduced adverse drug events and increase drug effectiveness. Our aim was to quantify the clinical effectiveness of genotype‐guided prescribing. Methods Three electronic databases were searched from January 1980 through December 2013. Studies were eligible if they were RCTs comparing genotype‐guided prescribing with non‐genetic informed prescribing, reported drug specific adverse drug events and clinical effectiveness outcomes. Two reviewers independently screened titles and abstracts, extracted data and assessed study quality. Meta‐analyses of specific outcomes were conducted where data allowed. Results Fifteen studies, involving 5688 patients and 19 drugs, met the inclusion and exclusion criteria. Eight studies had statistically significant results for their primary outcome in favour of genotype‐guided prescribing. Nine studies evaluated genotype‐guided warfarin dosing. Analysis of percentage of time in therapeutic international normalized ratio range (1952 individuals) showed a statistically significant benefit in favour of genotype‐guided warfarin dosing (mean difference = 6.67; 95% CI 1.34, 12.0, I2 = 80%). There was a statistically significant reduction in numbers of warfarin‐related minor bleeding, major bleeding and thromboembolisms associated with genotype guided warfarin dosing, relative risk 0.57 (95% CI 0.33, 0.99; I2 = 60%). It was not possible to meta‐analyze genotype‐guided dosing for other drugs. Of the six non‐warfarin genotype‐guided trials, two demonstrated a statistically significant benefit for their primary outcome, odds ratio 0.03 (95% CI 0.00, 0.62, P < 0.001) for abacavir. Conclusions There is evidence of improved clinical effectiveness associated with genotype‐guided warfarin dosing.